2009
DOI: 10.1007/s12160-009-9130-7
|View full text |Cite
|
Sign up to set email alerts
|

Defining Internet-Supported Therapeutic Interventions

Abstract: These categories may now serve as guiding definitions and related terminologies for further research and development in this emerging field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
535
0
38

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(575 citation statements)
references
References 96 publications
(100 reference statements)
2
535
0
38
Order By: Relevance
“…Online interventions consist of predominantly self-guided interactive programs designed to produce cognitive, affective and/or behavioural changes [10]. Based on empirically supported face-to-face treatments, most commonly cognitive behaviour therapy (CBT), these interventions require active engagement through the completion of web-based worksheets and activities [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Online interventions consist of predominantly self-guided interactive programs designed to produce cognitive, affective and/or behavioural changes [10]. Based on empirically supported face-to-face treatments, most commonly cognitive behaviour therapy (CBT), these interventions require active engagement through the completion of web-based worksheets and activities [10].…”
mentioning
confidence: 99%
“…Based on empirically supported face-to-face treatments, most commonly cognitive behaviour therapy (CBT), these interventions require active engagement through the completion of web-based worksheets and activities [10]. Compared to educational (information only) programs, online self-guided interventions have demonstrated efficacy across a range of psychological health conditions [11,12], including cancer distress [11][12][13].…”
mentioning
confidence: 99%
“…This support can take many forms, including reminders and personalised feedback (Barak et al, 2009). For example, Berger, Hohl, and Caspar (2009) reported that combining I-CBT with therapist contact via email resulted in significant reductions in social anxiety, which was maintained six months after the intervention.…”
mentioning
confidence: 99%
“…A falta de consenso nas definições adotadas faz com que termos como web-based therapy, e-therapy, cybertherapy, eHealth, e-Interventions, computer-mediated interventions e online counseling sejam utilizados como sinônimos, quando designam práticas diferentes. Uma padronização da terminologia faz-se necessária para maior discriminação do campo (Barak, Klein, & Proudfoot, 2009). …”
unclassified
“…Igualmente, o feedback varia em termos de quantidade, frequência e rapidez de resposta. O feedback humano tende a ser mais adaptado às circunstâncias do paciente em comparação com o automático (Barak et al, 2009). …”
unclassified